New silk roads: the present and future of the world - Frankopan, Peter (Chennai Thomson Press, 2018)
The New Silk Roads brings this story up to date, addressing the present and future of a world that is changing dramatically. Following the Silk Roads eastwards, from Europe through to China, by way of Russia and the Middle East, The New Silk Roads provides a timely reminder that we live in a world that is profoundly interconnected.
Keywords: Roads